Europeanization of Turkey's Foreign Policy: The Case of Turkey's Mediation in the Israel–Palestine Conflict. Issue 6 (2nd November 2019) - Ayaz Avan, Esengül
ABSTRACT: This study investigates the Europeanization of Turkey's foreign policy by examining Turkey's mediating role in the Israel–Palestine dispute. The paper assesses whether, to what extent and how the EU shaped Turkey's mediating role in the conflict. It is concluded that Turkish political actors used the EU to justify certain policies and their relations with certain actors, which would otherwise be considered unacceptable. Given its indirect impact on Turkey's mediation, the EU's role in Turkish foreign policy should not be exaggerated. There seems to be no evidence in this case that Turkish foreign policy-makers internalized EU foreign-policy norms.